Maladjustment of bully-victims: validation with three identification methods. Issue 8 (13th September 2016) - Yang, An; Li, Xiang; Salmivalli, Christina
Abstract : Although knowledge on the psychosocial (mal)adjustment of bully-victims, children who bully others and are victimised by others, has been increasing, the findings have been principally gained utilising a single method to identify bully-victims. The present study examined the psychosocial adjustment of bully-victims (as compared with pure bullies and pure victims) identified by Olweus' global measures, peer nominations and a profile method based on Olweus' multiple measures of bullying/victimisation forms. The sample included 17, 586 students from grades 3 to 8 (9–15 years old) in Finland. Bully-victims formed the smallest group, whose subjective experience of maladjustment differed from that of the bullies, rather than that of the victims. Both the prevalence and the relative maladjustment of bully-victims varied across identification methods, gender and school level.